A novel tDCS control condition using optimized anesthetic gel to block peripheral nerve input - Kerstens, Silke; Orban de Xivry, Jean-Jacques; Mc Laughlin, Myles (Frontiers in Neurology, 2022)
Recent studies indicate that some transcranial direct current stimulation (tDCS) effects may be caused by indirect stimulation of peripheral nerves in the scalp rather than the electric field in the brain. To address this we developed a novel tDCS control condition in which peripheral input is blocked using topical anesthetics. We developed a compounded anesthetic gel containing benzocaine/lidocaine (BL10) that blocks peripheral input during tDCS. In a blinded randomized cross-over study of 18 healthy volunteers (M/F), we compared the gel’s efficacy to EMLA and an inert placebo gel. Subjects used a visual analogue scale (VAS) to rate the stimulation sensation in the scalp produced by 10 seconds of 2mA tDCS every 2 minutes during 1 hour. In an additional in-vitro experiment, the effect of a DC current on gel resistivity and temperature was investigated. Both the BL10 and EMLA gel, lowered the stimulation sensations compared to the placebo gel. The BL10 gel showed a tendency to work faster than the EMLA gel with reported sensations for the BL10 gel being lower than for EMLA for the first 30 minutes. The DC current caused a drastic increase in gel resistivity for the EMLA gel, while it did not affect gel resistivity for the BL10 and placebo gel, nor did it affect gel temperature. Topical anesthetics reduce stimulation sensations by blocking peripheral nerve input during tDCS. The BL10 gel works faster and is more electrically stable than EMLA gel.